2018
DOI: 10.1051/ocl/2017055
|View full text |Cite
|
Sign up to set email alerts
|

Exploring amazonian fats and oils blends by computational predictions of solid fat content

Abstract: -The Amazon region has richness of oleaginous plants that have attracted attention due to its unique properties. Integrating local communities in an economic chain of valorization of fats/oils can enhance the social dimension of local oleaginous industry sustainability. Given the large diversity of raw materials and the possibility to mix them in different proportions, an experimental effort must be done to evaluate the physical properties of such feedstocks. In this context, the development of computational t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
8
0
3
Order By: Relevance
“…Compositions obtained by this study for Brazil nut oil and murumuru fat were in agreement with those reported by Saraiva, Cabral, Eberlin, and Catharino (2009), who characterized the TAG profile of Amazon vegetable oils and fats by mass spectrometry. The theoretical TAG profile of tucuma kernel oil described here was also in agreement with the one reported by Santos, Morgavi, and Le Roux (2018). These authors also applied a computational tool for estimating TAG profiles of Amazon fatty products.…”
Section: Fa Composition Tag Profile and Nutritional Quality Indexessupporting
confidence: 88%
“…Compositions obtained by this study for Brazil nut oil and murumuru fat were in agreement with those reported by Saraiva, Cabral, Eberlin, and Catharino (2009), who characterized the TAG profile of Amazon vegetable oils and fats by mass spectrometry. The theoretical TAG profile of tucuma kernel oil described here was also in agreement with the one reported by Santos, Morgavi, and Le Roux (2018). These authors also applied a computational tool for estimating TAG profiles of Amazon fatty products.…”
Section: Fa Composition Tag Profile and Nutritional Quality Indexessupporting
confidence: 88%
“…Desse último, ao ser submetido ao processo de hidrólise, obtém-se o ácido mirístico, que de modo geral possui propriedades emolientes, hidratantes e capacidade de proteção da pele contra os efeitos de irritabilidade de sabões (SALVADEGO, 2009;. A avaliação das propriedades físico-químicas compiladas na tabela 3 demonstra que os altos índices de saponificação seriam indicativos do tamanho da cadeia dos ácidos graxos presentes, demonstrando a prevalência de AG com baixo peso molecular (LACERDA JÚNIOR; DA SILVA, 2009;SANTOS et al, 2018).…”
Section: Ucuúba -unclassified
“…Desse último, ao ser submetido ao processo de hidrólise, obtém-se o ácido mirístico, que de modo geral possui propriedades emolientes, hidratantes e capacidade de proteção da pele contra os efeitos de irritabilidade de sabões (SALVADEGO, 2009;SILVA et al, 2014). A avaliação das propriedades físico-químicas compiladas na tabela 3 demonstra que os altos índices de saponificação seriam indicativos do tamanho da cadeia dos ácidos graxos presentes, demonstrando a prevalência de AG com baixo peso molecular (LACERDA JÚNIOR;DA SILVA, 2009;SANTOS et al, 2018). As diclofenac sodium is an anti-inflammatory drug and taken worldwide, along the last decades.…”
Section: Ucuúba -unclassified